2017
DOI: 10.7150/ijbs.23000
|View full text |Cite
|
Sign up to set email alerts
|

Specific Deletion of β-Catenin in Col2-Expressing Cells Leads to Defects in Epiphyseal Bone

Abstract: The role of canonical Wnt/β-catenin signaling in postnatal bone growth has not been fully defined. In the present studies, we generated β-catenin conditional knockout (KO) mice and deleted β-catenin in Col2-expressing chondrocytes and mesenchymal progenitor cells. Findings from analyzing the β-cateninCol2CreER KO mice revealed severe bone destruction and bone loss phenotype in epiphyseal bone, probably due to the increase in osteoclast formation and the accumulation of adipocytes in this area. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Tibiae were harvested and fixed in 10% neutral‐buffered formalin for 3 days and decalcified for 14 days in 14% EDTA and then paraffin‐embedded. Three‐micrometer sections were cut and alcian blue/H&E orange G staining and tartrate‐resistant acid phosphatase (TRAP) staining were performed (Shu et al, ; B. Wang et al, ; Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Tibiae were harvested and fixed in 10% neutral‐buffered formalin for 3 days and decalcified for 14 days in 14% EDTA and then paraffin‐embedded. Three‐micrometer sections were cut and alcian blue/H&E orange G staining and tartrate‐resistant acid phosphatase (TRAP) staining were performed (Shu et al, ; B. Wang et al, ; Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Wnt signaling plays critical role in regulating MSC fate. Activation of Wnt signaling stimulates myogenesis and inhibits adipogenesis . It has been reported that Wnt signaling promotes the differentiation of adipose progenitor cells into fibroblastic cells rather than adipocytes .…”
Section: Wnt Signaling In Aging Adipose Tissuementioning
confidence: 99%
“…Activation of Wnt signaling stimulates myogenesis and inhibits adipogenesis. [149][150][151][152] It has been reported that Wnt signaling promotes the differentiation of adipose progenitor cells into fibroblastic cells rather than adipocytes. 138 Leptin is synthesized by mature adipocytes in response to changes in body fat mass and nutritional status.…”
Section: Wnt Signaling In Aging Adipose Tissuementioning
confidence: 99%
“… 30 Furthermore, Col2‐specific knockout of β‐catenin led to bone destruction in knee joint area, large numbers of osteoclasts and adipocytes were accumulated in the area underneath of growth plate. 31 In a study using Col2a1‐Wnt16 and Col2a1‐Cre;Wnt16 fl/fl mice as well as 3D chondrocyte pellet culture with technology of adenovirus Wnt16 manipulation, Tong and colleagues reveal that Wnt16 inhibit chondrocyte hypertrophy via activating PCP/JNK and cross‐talking with mTORC1‐PTHrP pathway. 32 Chen et al demonstrated that cyclin D1 stimulated proliferation and apoptosis of the chondrocyte through increasing the expression of Wnt3/β‐catenin rather than Wnt10a/β‐catenin signalling pathway.…”
Section: β‐Catenin Signalling In Oa Cartilagementioning
confidence: 99%